Educational Programs for the Management of Childhood Atopic Dermatitis: An Integrative Review - Yunmi Lee, PhD, RN; Jina Oh, PhD, RN (Asian Nursing Research, 2015)
Purpose: The purpose of this integrative review was to synthesize the available research on educational programs for the management of childhood atopic dermatitis. Methods: Articles were retrieved from the following databases: Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, PubMed, and SCOPUS. Inclusion criteria were publication in the English or Korean language prior to March 2013, as a peer-reviewed empirical study focused on educational programs for childhood atopic dermatitis. Results: Fifteen papers met the inclusion criteria. Four themes were derived from the data: (a) children of all ages and symptom severity, and their families as learners; (b) well-trained and family-preferred health professionals as educators; (c) long-term follow-up with diverse interventions as educational methods; and (d) quality of life for the child and family as educational goals. Conclusions: This review indicates the challenges that health professionals face in improving symptoms of atopic dermatitis. The identified strategies can be used in the development of more effective evidence-based programs. Future studies should focus on the development and evaluation of educational programs that include these themes.